Design and building of solder and TSV daisy chain electromigration tester - Ser, Edwin Wei Jun. (2011)
Through Silicon Via (TSV) is a hot topic in today’s 3D Integrated Circuit. In order for TSV to be used commercially, reliable evaluation of TSV is necessary, especially on its electromigration. To assess the electromigration reliability of different types of interconnects experimentally, EM tests that involve the monitoring of DUT’s resistance under high temperature and current stress conditions are conducted. The test structure will be a failure if its resistance reaches a predetermined value.